Efficiency Optimisation of an Experimental PEM Fuel Cell System via Super Twisting Control - Kunusch, Cristian (2010)
A robust control solution is proposed to solve the air supply control problem in autonomous polymer electrolyte membrane fuel cells (PEMFC) based systems. Different second order sliding mode (SOSM) controllers are designed using a model of a laboratory test fuel cell generation system. Very good simulation results are obtained using such algorithms, showing the suitability of the SOSM approach to PEMFC stack breathing control. Subsequently, for experimental validation, a controller based on one of the previously assessed SOSM algorithms, namely a Super Twisting, is successfully implemented in the laboratory test bench. Highly satisfactory results are obtained, regarding dynamic behaviour, regulation error and robustness to uncertainties and external disturbances.